On a Cohesive Set of Requirements Engineering Terms. Issue 2 (19th May 2017) - Ryan, Michael J.; Wheatcraft, Louis S.
ABSTRACT: The purpose of a requirement expression is to transform the needs of various entities into a formal language such that the intent is clearly understood by all involved. Although many sources provide definitions of the terms associated with a requirement expression, few contain guidance as to the process of developing a requirement, there are only occasional agreements on common definitions, and the defined terms are too narrowly focused to be useful across the full requirements engineering domain. This paper develops a cohesive set of definitions of the terms associated with a requirement expression. First, a framework for the transformation of needs into requirements is discussed and existing definitions are presented from the major relevant sources. These definitions are then analyzed and an integrated set of definitions is developed for the key terms associated with a requirements expression: entity; need; requirement expression; requirement statement; characteristics of a well‐formed requirement statement and a well‐formed set of requirements; and requirement attributes that, along with the requirement statement itself, comprise a well‐formed requirement expression.